Hypertension and Subsequent Genitourinary and Gynecologic Cancers Risk. Issue 16 (April 2015) - Sun, Li-Min; Kuo, Huang-Tsung; Jeng, Long-Bin; Lin, Cheng-Li; Liang, Ji-An; Kao, Chia-Hung; Huo., Jinhai
<x xml:space="preserve">Abstract</x> Abstract Although a relationship between hypertension and the development of renal cancer and other types of cancer have been proposed for decades, the results of epidemiologic studies remain inconclusive. This study was conducted to evaluate the association between hypertension and genitourinary and gynecologic cancers in Taiwan. In this study, we conducted a populated-based retrospective cohort study by using data from the Taiwanese National Health Insurance program. The study period was from 2000 to 2011, and the cohort comprised 111, 704 insurants: 57, 961 patients with hypertension and 53, 743 patients without hypertension. A Cox proportional hazard regression analysis was performed to estimate the effects of hypertension on genitourinary and gynecologic cancers risk. Among the patients with hypertension, the risks of developing renal and uterine corpus cancers were significantly higher in the hypertension group than they were in the nonhypertension group. Further stratified analyses by sex, age, and hypertension duration revealed distinct cancer-specific patterns. Higher cancer risk appears to be more obvious among younger hypertensive patients with longer follow-up time. The results of this study indicate that Taiwanese patients with hypertension have higher risks for some types of cancer, and cancer-specific patterns vary by sex, age, and hypertension duration.